2015
DOI: 10.1080/02640414.2015.1127987
|View full text |Cite
|
Sign up to set email alerts
|

Differences in pedalling technique between road cyclists of different competitive levels

Abstract: The purpose of this study was to compare the pedalling technique in road cyclists of different competitive levels. Eleven professional, thirteen elite and fourteen club cyclists were assessed at the beginning of their competition season. Cyclists' anthropometric characteristics and bike measurements were recorded. Three sets of pedalling (200, 250 and 300 W) on a cycle ergometer that simulated their habitual cycling posture were performed at a constant cadence (~90 rpm), while kinetic and kinematic variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 37 publications
2
21
0
3
Order By: Relevance
“…Besides, in this work the authors determined indicators of bilateral asymmetry of pedaling force and EMG. These results show that cyclists can "re-switch" between sitting and standing positions during competitions, for increasing race efficiency in different situations [6]; Professional cyclists increase pulling force in the phase of recreation for sustaining the same output power [12]; Effectiveness of cycling is influenced by profiles of foot angle. This factor is one of the most important and directly correlates with effective force, applied to bicycle [32].…”
Section: Introductionmentioning
confidence: 89%
“…Besides, in this work the authors determined indicators of bilateral asymmetry of pedaling force and EMG. These results show that cyclists can "re-switch" between sitting and standing positions during competitions, for increasing race efficiency in different situations [6]; Professional cyclists increase pulling force in the phase of recreation for sustaining the same output power [12]; Effectiveness of cycling is influenced by profiles of foot angle. This factor is one of the most important and directly correlates with effective force, applied to bicycle [32].…”
Section: Introductionmentioning
confidence: 89%
“…The results from this study showed that power output measured by the customized pedal force-motion tracking system was substantially different from the pre-set power output from the cycle ergometer. Although the Lode Excalibur ergometer has been widely used for measurements of power output [7,18] and torque [40], we were unable to find studies on the validity of these measures taken from a calibration rig, which is the gold standard in assessing accuracy of power meters [41]. Therefore, a proportion of the differences between pedals and the cycle ergometer could be due to the previously referred instantaneous control of the wheel resistance when cadence fluctuated.…”
Section: Within-session Reliabilitymentioning
confidence: 97%
“…La utilización de este índice se basa en el concepto que toda la fuerza que se aplica en el pedal debería poder ser efectiva, lo cual es poco probable, ya que para conseguirlo el ciclista debería aplicar la máxima fuerza vertical hacia el suelo durante la fase propulsiva o de bajada del pedal, y la máxima fuerza vertical hacia arriba durante el recobro o fase de subida del pedal. Además, es posible que durante la propia fase de bajada del pedal interese que parte de la fuerza resultante no sea efectiva, con el objetivo de hacer que el vector de fuerza de reacción en el pedal pase más cerca de todas las articulaciones implicadas en el pedaleo Garcia-Lopez, et al, 2009;Garcia-Lopez, Ogueta-Alday, Díez-Leal, et al, 2014;Gonzalez & Hull, 1989;). De acuerdo con algunos autores, este índice de técnica de pedaleo es más que discutible (Leirdal & Ettema, 2011a).…”
Section: íNdices De Técnica De Pedaleounclassified
“…Sin embargo, otros estudios que lo han realizado también de forma aguda durante más tiempo (45 minutos) han demostrado que este tipo de estrategia sería capaz de mantenerse en el tiempo sin penalizar con el aumento del gasto de energía . No existiendo trabajos que lo hayan valorado a largo plazo, lo que sí parece claro es que los ciclistas profesionales son capaces de generar mayor proporción de fuerza o impulso positivo para pedalear a la misma intensidad que los ciclistas de categorías inferiores, presentando menores valores de fuerzas negativas durante el recobro, es decir, realizando un ascenso activo del pedal (Garcia-Lopez, Ogueta-Alday, Díez-Leal, et al, 2014).…”
Section: íNdices De Técnica De Pedaleounclassified
See 1 more Smart Citation